Comparison of penetrating thoracic traumas in patients with gunshot and stab wounds in an emergency department - Saylam, Nil; Algedik Gürsoy, Deniz; Şahin, Ali; Aydın, Ufuk; Özüçelik, Doğaç Niyazi (The European Research Journal, 2020)
Objectives: Thoracic trauma is among the most important causes of mortality in emergency departments. In this study of penetrating stab wounds (PSWs) and gunshot wounds (GSWs) admitted to the emergency department with penetrating thoracic trauma cases clinical findings, emergency treatment approaches and survivals were compared with literature information. Methods: One hundred fifty-two patients who applied to Bakırköy Dr. Sadi Konuk Training and Research Hospital Emergency Department with penetrating thoracic trauma on 1 January 2014 and 31 December 2014 were evaluated retrospectively the patients. SPSS 22.0, NY, USA program was used in the analyzes. Results: Patients administered with PSW were 79.6%, with GSW were 20.4%. Patients in the group GSW were admitted to the emergency department with more serious symptoms than patients in the group PSW (Triage level 2, GSW: 87.1%, PSW: 62.8% and Triage level 3, GSW: 12.9% vs. PSW: 37.2%), (p = 0.010). Hemothorax (25.8%) in PSW patients and pneumothorax (40.5%) in GSW patients was detected more frequently. Surgical treatment was performed in 14.9% of patients with PSW, tube thoracostomy was performed in 24%, and 62.82% were treated with conservative treatment. Surgical treatment was performed in 35.5% of GSW patients and tube thoracostomy was performed in 29%, and 48.4% were treated with conservative treatment (p > 0.05). Conclusion: Despite the lower incidence of GSW than PSW in emergency departments, GSW require more surgical intervention and have a higher mortality rate.